Extreme Asceticism, Medicine and Pure Land Faith in the Life of Shuichi Muno (1683-1719) - Groner, Paul (Japanese religions, 2012)
Munō’s (1683-1719) biography is contrary to some of our standard views of Jōdo-shū practice. He embodies unshakeable faith, but this leads him to undertake some of the most severe ascetic practices found in monks of any school; these include auto-castration and austerities that lead to an early death. Munō records how he increases the numbers of recitation of the nenbutsu to almost unbelievable numbers, ignoring his physical needs in the process as he longs for death and subsequent birth in the Pure Land. His sincerity made him eff ective at spreading Pure Land practice among the impoverished and ill, including lepers. He participated in nursing the ill, sometimes prescribing the use of nenbutsu as a cure and at other times telling people that they should prepare for death. His detailed records of these people give us an unusually vivid picture of the people who received his ministrations; these included lepers, the blind, the deaf and those bothered by bad dreams. Munō also kept records of his own dreams. Finally, Munō compiled a list of guidelines for those who were inspired by him, telling them how they should behave and practice. His followers carefully recorded the details of his death in a manner found in many Pure Land texts.